2023
DOI: 10.1093/mnras/stad235
|View full text |Cite
|
Sign up to set email alerts
|

The drifting subpulse and nulling of PSR B0820 + 02 observed with FAST

Abstract: PSR B0820 + 02 is known to exhibit the subpulse drifting phenomenon, which carries vital information about the pulsar radiation process. In this work, we studied the subpulse drifting of PSR B0820 + 02 at a central frequency of 1250 MHz using the Five-hundred-meter Aperture Spherical radio Telescope (FAST). Thanks to the superior sensitivity of FAST, we found that PSR B0820 + 02 shows four distinct subpulse drifting modes (A, B, C, and D), the last three of which have not been reported before. The drifting per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…, a small fluctuation in ¢ P 3 leads to a significant change in P 3 . Many studies have affirmed the behavior of multidrift and the drift direction change of pulsars due to the aliasing effect (e.g., Esamdin et al 2005;Szary et al 2022;Zhi et al 2023a). For PSR B2110+27, Figure 1 shows that its drift band direction consistently changes, indicating that the subpulse drifting behavior is frequently affected by the aliasing effect.…”
Section: Aliasing Effectmentioning
confidence: 99%
See 2 more Smart Citations
“…, a small fluctuation in ¢ P 3 leads to a significant change in P 3 . Many studies have affirmed the behavior of multidrift and the drift direction change of pulsars due to the aliasing effect (e.g., Esamdin et al 2005;Szary et al 2022;Zhi et al 2023a). For PSR B2110+27, Figure 1 shows that its drift band direction consistently changes, indicating that the subpulse drifting behavior is frequently affected by the aliasing effect.…”
Section: Aliasing Effectmentioning
confidence: 99%
“…The gradual establishment and deployment of highly sensitive telescopes are enlarging the catalog of subpulsating drift pulsars. The exceptional quality of these observations is enabling us to discern details that were once indistinguishable (Zhi et al 2023a;Xu et al 2024).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For a long time, only a handful of pulsars were known to exhibit mode changing associated with subpulse drifting, with prominent examples being PSR B0031-07 (Huguenin et al 1970;Vivekanand & Joshi 1997;Smits et al 2005;McSweeney et al 2017), PSR B0809+74 (van Leeuwen et al 2002;Hassall et al 2013;Basu et al 2023a), PSR B0943+10 (Suleymanova et al 1998;Backus et al 2011), PSR B1237+25 (Backer 1970;Srostlik & Rankin 2005), PSR B1918+19 (Hankins & Wolszczan 1987;Rankin et al 2013), PSR B1944+17 (Deich et al 1986;Kloumann & Rankin 2010), PSR B2303+30 (Redman et al 2005), and PSR B2319+60 (Wright & Fowler 1981;Rahaman et al 2021). In recent years, dedicated studies of the single pulse emission from pulsars using instruments like the Giant Metrewave Radio Telescope (GMRT), Murchison Widefield Array, FAST, etc., have found several other examples of subpulse drifting associated with mode changing, e.g., PSR J0026-1955J0026- (McSweeney et al 2022Janagal et al 2023), PSR B0820+02 (Zhi et al 2023), PSR J1110-5637 (Dang et al 2022), PSR J1727-2739 (Wen et al 2016;Basu et al 2021;Rejep et al 2022), PSR B1819-22 (Basu & Mitra 2018a;Janagal et al 2022), and PSR B2003-08 (Basu et al 2019b). In the above list, only three pulsars, PSR B1237+25, PSR B2003-08, and PSR B2319+60, have c Q/M profile types signifying the central LOS traverse across the emission beam.…”
Section: Introductionmentioning
confidence: 99%
“…In general, subpulse drifting can be represented by three drift parameters: the vertical band spacing at the phase of the same pulse (P 3 ), the horizontal time interval between successive drift bands (P 2 ), and the drift rate (Δf = P 2 /P 3 ). Since its discovery, various unusual behaviors of subpulse drifting have been reported, which have challenged the traditional carrousel circulation models (e.g., Wen et al 2016;Dang et al 2022;Xu et al 2024;Zhi et al 2023). Several studies have found some evidence of a link between nulling and subpulse drifting-for example, the drift rate changes after the null state (van Leeuwen et al 2003;.…”
Section: Introductionmentioning
confidence: 99%